2017
DOI: 10.1016/j.jrras.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An overview of radon concentration in Malaysia

Abstract: It is known that the inhalation and ingestion of radon gas could lead to the primary health risks for lung and stomach cancers. Besides the health hazards of radon gas, it has different geological applications. In this context, numerous studies have been reported all over the world. Different research groups in Malaysia have also conducted and reported numerous studies since several decades. However, these studies are scattered and need to be compiled for future studies in Malaysia. The main emphasis is to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A large summary of radon measurements performed in Malaysia between 1994 and 2017 was presented by Ahmad et al [114]. They reported that indoor radon concentrations varied between minimum and maximum values from 11 to 3075 Bq m −3 .…”
Section: Malaysia (Iii)mentioning
confidence: 99%
“…A large summary of radon measurements performed in Malaysia between 1994 and 2017 was presented by Ahmad et al [114]. They reported that indoor radon concentrations varied between minimum and maximum values from 11 to 3075 Bq m −3 .…”
Section: Malaysia (Iii)mentioning
confidence: 99%
“…The influence of different geological units on natural radioactivity enables us to estimate the radiological risks that humans are exposed to and determine the background baseline values of natural radioactivity (Uyanik et al 2013 ; Kazumasa et al 2020 ; Ofomola et al 2023 ). The inhalation of radon and thoron causes lung cancer by emitting high ionising alpha particles that interact with biological tissue in the lungs and damage the DNA of the lungs (Ahmad et al 2017 ). Gamma, beta and alpha radiation are the standard forms of radiation produced by radionuclide decay.…”
Section: Introductionmentioning
confidence: 99%
“…Some are operational, demand energy, and have a continuous record of Radon gas concentration and variations throughout the measurement time (Li et (Sainz et al 2021). Since the maximum Radon concentration is achieved while the space in question is devoid of air ventilation (for example, when all windows and joints are closed), the brief measurement taken during this time should be considered more signi cant than the average annual Radon amount (Ahmad et al 2021).…”
Section: Introductionmentioning
confidence: 99%